2022
DOI: 10.3389/fnbeh.2022.879168
|View full text |Cite
|
Sign up to set email alerts
|

General and Specific Aversive Modulation of Active Avoidance Require Central Amygdala

Abstract: Three studies provide evidence that the central nucleus of the amygdala, a structure with a well-established role in conditioned freezing, is also required for conditioned facilitation of instrumental avoidance in rats. First, the immediate early gene c-Fos was measured following the presentation of a previously shock-paired tone in subjects trained either on an unsignaled avoidance task or not (in addition to tone only presentations in naïve controls). Significantly elevated expression of c-Fos was found in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge while there are no previous imaging studies that have documented Pavlovian value signals in the vmPFC or dorsal ACC, recent research work has reported positive and negative valence effects in these regions consistently 36 with our findings (Algermissen et al, 2022). Also, outcome-locked vmPFC activity has been shown to scale with greater Pavlovian influence as a function of diminished environmental controllability (Gershman et al, 2021) (Campese et al, 2015;Campese et al, 2017;Kim et al, 2022). Using congruent appetitive PIT paradigms previous neuroimaging studies have found that BOLD activity in the nucleus accumbens (Talmi et al, 2008;Mendelsohn et al, 2014), amygdala (Talmi et al, 2008;Prevost et al, 2012;Mendelsohn et al, 2014) and striatum (Bray et al, 2008;Prevost et al, 2012) is correlated with appetitive PIT effects.…”
mentioning
confidence: 99%
“…To the best of our knowledge while there are no previous imaging studies that have documented Pavlovian value signals in the vmPFC or dorsal ACC, recent research work has reported positive and negative valence effects in these regions consistently 36 with our findings (Algermissen et al, 2022). Also, outcome-locked vmPFC activity has been shown to scale with greater Pavlovian influence as a function of diminished environmental controllability (Gershman et al, 2021) (Campese et al, 2015;Campese et al, 2017;Kim et al, 2022). Using congruent appetitive PIT paradigms previous neuroimaging studies have found that BOLD activity in the nucleus accumbens (Talmi et al, 2008;Mendelsohn et al, 2014), amygdala (Talmi et al, 2008;Prevost et al, 2012;Mendelsohn et al, 2014) and striatum (Bray et al, 2008;Prevost et al, 2012) is correlated with appetitive PIT effects.…”
mentioning
confidence: 99%